Reference production in Mandarin–English bilingual preschoolers: Linguistic, input, and cognitive factors - Zhou, Jiangling; Mai, Ziyin; Cai, Qiuyun; Liang, Yuqing; Yip, Virginia (Frontiers in Psychology, 2022)
Reference in extended discourse is vulnerable to delayed acquisition in early childhood. Although recent research has increasingly focused on effects of linguistic, input, and cognitive factors on reference production, these studies are limited in number and the results are mixed. The present study provides insight into bilingual reference production by investigating how production of referring expressions in the two languages of preschool bilingual children may be influenced by structural similarities and differences between the languages, frequency of referring expressions in maternal input, amount of exposure to each of the languages, and working memory capacity. Using two stories in the Multilingual Assessment Instrument for Narratives (MAIN), we examined character introduction and reintroduction in oral narratives of 4- to 6-year-old Singaporean bilingual children acquiring Mandarin Chinese and English (n = 21), and in child-directed speech of the mothers (n = 17). The children’s language exposure, executive function and general bilingual proficiency were also recorded or directly tested through structured interviews with the parents or standardized assessments with the children. Data collection was conducted remotely in real time over a video-conferencing platform, supplemented by on-site audio recording to ensure sound quality. Results showed prolonged development in the production of felicitous REs for first mentions and over-reliance on overt marking of definiteness in our bilingual children. Mixed modelling revealed that frequency of felicitous REs in the input predicted children’s production of felicitous REs across languages and discourse functions, with a modulating effect of working memory. Overall, our findings are consistent with previous ones in that reference production is vulnerable in early Mandarin-English bilinguals in a multilingual society. This study also presents novel evidence that structural frequency in the input interacts with working memory in shaping patterns of reference production in bilingual children.